2021
DOI: 10.3390/ijerph18041487
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Mental Health Sequelae of Climate Change Extremes: A Case Study of the Deadliest Californian Wildfire

Abstract: Introduction. Weather-related disasters, such as wildfires exacerbated by a rise in global temperatures, need to be better studied in terms of their mental health impacts. This study focuses on the mental health sequelae of the deadliest wildfire in California to date, the Camp Fire of 2018. Methods. We investigated a sample of 725 California residents with different degrees of disaster exposure and measured mental health using clinically validated scales for post-traumatic stress disorder (PTSD), major depres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 54 publications
6
65
0
5
Order By: Relevance
“…Studies have looked at other outcomes or symptoms associated with PTSD post-wildfire including sleep disturbance and insomnia, anger, attachment style, interpersonal violence, and a term known as vicarious traumatization which is the development of PTSD symptoms from indirect trauma exposure [ 43 , 46 , 48 , 50 , 51 , 62 , 70 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies have looked at other outcomes or symptoms associated with PTSD post-wildfire including sleep disturbance and insomnia, anger, attachment style, interpersonal violence, and a term known as vicarious traumatization which is the development of PTSD symptoms from indirect trauma exposure [ 43 , 46 , 48 , 50 , 51 , 62 , 70 , 73 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our literature search did not reveal a review specific to risk factors for developing PTSD post-bushfire, but such factors have been investigated by several primary studies. In adults, demographic factors such as female gender, widowed status, or fewer years of education, lower socioeconomic status, and non-caucasian ethnicity are associated risk factors, although gender was not always been found to be significant [ 26 , 32 , 69 , 73 , 78 ]. Trauma-related factors significant to increasing one’s risk of post-wildfire PTSD include personal witnessing of burning homes, having fear for one’s life or lives of loved ones, losing a loved one, significant property damage, or feeling a lack of support from family, friends, and/or the government [ 22 , 26 , 32 , 34 , 42 , 57 , 62 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Belleville and colleagues [ 40 ] also found that sleep disturbances, sleep quality and insomnia were significantly associated with PTSD three months post-fires ( p < 0.01). Furthermore, higher levels of sleep disturbances on the Patient-Reported Outcomes Measurement Information System (PROMIS) were associated with higher scores on the PTSD-Checklist (PCL-5, Blevins et al, 2015) [ 44 ].…”
Section: Resultsmentioning
confidence: 99%